The combination of chemotherapy and immune checkpoint inhibitors in recurrent extensive-stage small cell lung cancer: a case report - Chunxiu Hu; Mingtu Zhang; Min Fang; Yi Liu; Zhengqi Yang (Journal of Cardiothoracic Surgery)
Abstract Small cell lung cancer (SCLC) accounts for approximately 15% of all lung cancer cases and is characterized by high malignancy, rapid progression, and poor prognosis. Here, we report a case of a 58-year-old female patient who was initially diagnosed with extensive-stage SCLC (ES-SCLC) with liver metastasis. The patient underwent etoposide and cisplatin (EP) chemotherapy combined with local radiotherapy and achieved a complete response. The progression-free survival reached 48 months, and upon relapse, the patient received EP chemotherapy combined with the programmed cell death protein 1 (PD-1) inhibitor, tislelizumab, as immunotherapy. During the treatment period, the patient experienced immune-related pancreatitis, but the symptoms were relieved with timely intervention and treatment. As of January 2, 2024, the patient’s overall survival exceeded 95 months. This case highlights the potential efficacy of the combination of chemotherapy and immunotherapy in recurrent ES-SCLC patients and underscores the importance of close monitoring and management of immune-related adverse reactions. The study provides valuable insights into the application of personalized treatment in lung cancer management and offers new possibilities for extending patient survival.